Ethics, Life and Health: a prospective reflection - Lepargneur, Hubert (O Mundo da Saúde, 2007)
This prospective study on Bioethics makes efforts to point out themes that will probably capture attention and motivate research and/or discussions. All anticipating reflection is risky and will certainly be corrected as the future unfolds. There is no trying to present an ideal picture for the Bioethics of the future, that is, an expression of the author's personal Bioethics, which is another genre. What will remain are the American tendency - that grounds reflections on some principles, and employs criteria of a more pragmatic type - and the European one - that looks for a grounding anthropology, more philosophical but not unified, which aims to develop guidelines able to give to the possible and desirable future directions that are more coherent.